2006
DOI: 10.1073/pnas.0511189103
|View full text |Cite
|
Sign up to set email alerts
|

Disc1 is mutated in the 129S6/SvEv strain and modulates working memory in mice

Abstract: Disrupted-In-Schizophrenia (DISC1) is a leading candidate schizophrenia susceptibility gene. Here, we describe a deletion variant in mDisc1 specific to the 129S6͞SvEv strain that introduces a termination codon at exon 7, abolishes production of the full-length protein, and impairs working memory performance when transferred to the C57BL͞6J genetic background. Our findings provide insights into how DISC1 variation contributes to schizophrenia susceptibility in humans and the behavioral divergence between 129S6͞… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
251
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(266 citation statements)
references
References 26 publications
8
251
2
Order By: Relevance
“…Evidence that many of the DISC1 isoforms in C57BL/6J mice are also expressed in 129S6/SvEv mice Recently, Koike et al 1 identified a 25-bp deletion in a coding exon of the Disrupted-In-Schizophrenia (DISC1) gene in the 129S6/SvEv strain, which was also confirmed at the genomic level for all extant 129 mouse inbred substrains. 2 This mutation could interfere with the production of the full-length DISC1 protein.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Evidence that many of the DISC1 isoforms in C57BL/6J mice are also expressed in 129S6/SvEv mice Recently, Koike et al 1 identified a 25-bp deletion in a coding exon of the Disrupted-In-Schizophrenia (DISC1) gene in the 129S6/SvEv strain, which was also confirmed at the genomic level for all extant 129 mouse inbred substrains. 2 This mutation could interfere with the production of the full-length DISC1 protein.…”
mentioning
confidence: 86%
“…Immunoprecipitation with the mExon3 antibody followed by detection of the precipitates with the D27 antibody indicates that these two independent antibodies detect the same DISC1 molecule at 100 kDa, but an additional DISC1 band is detected by D27 at 105 kDa (Figure 1c). Therefore, this suggests that the antibody generated by Koike et al 1 might specifically detect a unique isoform of DISC1 at 100 kDa that is lost by the 25-bp deletion. Selective detection of this unique isoform in the immunoprecipitates with immunoglobulin G (IgG) from brain extracts of C57BL/6J, but not from those of 129S6/ SvEv, suggests that this isoform has a specific binding affinity to IgG (Supplementary Figure 4).…”
mentioning
confidence: 95%
See 3 more Smart Citations